Proceedings of the 4th International ICST Conference on Pervasive Computing Technologies for Healthcare 2010
DOI: 10.4108/icst.pervasivehealth2010.8888
|View full text |Cite
|
Sign up to set email alerts
|

A user centred approach for developing Brain-Computer Interfaces

Abstract: Purpose The study aim was to develop a mobile application (app) supported by user preferences to optimise self-management of arm and shoulder exercises for upper-limb dysfunction (ULD) after breast cancer treatment. Methods Focus groups with breast cancer patients were held to identify user needs and requirements. Behaviour change techniques were explored by researchers and discussed during the focus groups. Concepts for content were identified by thematic analysis. A rapid review was conducted to inform the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…BCIs offer users various opportunities for social participation. One way is to include potential or actual BCI users in research and technology development processes [31][32][33]. Other studies have acknowledged the importance of social participation for users [21,24].…”
Section: "[…]mentioning
confidence: 99%
“…BCIs offer users various opportunities for social participation. One way is to include potential or actual BCI users in research and technology development processes [31][32][33]. Other studies have acknowledged the importance of social participation for users [21,24].…”
Section: "[…]mentioning
confidence: 99%
“…First, users may tend to report on the function they would want to have rather than to assess the usability of the access technology itself. [23,24] A user's desire to control a television or be on social media does notstrictly speaking -justify the development of a BCI. It does justify the development of accessible social media, but says little about the requirements of the access technology that should make this possible.…”
Section: Introductionmentioning
confidence: 99%
“…UCD seeks to bridge the gap between what the technical developers think would be useful to have on the system and what end users would actually like and use on the BCI [16]. Kübler et al [17] found than less that 10% of published research on BCI involved real end users.…”
Section: ____________________________________________________________mentioning
confidence: 99%